Fostering Digital Literacy by Using Powtoon as an Innovative Media in Physics Learning - Susilawati , Susilawati; Shandi, Tiara; Mahzum, Elmi; Musdar; Saminan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The 21st-century industrial revolution demands increased digital literacy among students. However, data shows that the digital literacy level of Indonesian students remains relatively low. This gap is challenging, especially in schools with limited access to technology-based learning media. This study aimed to examine the effectiveness of Powtoon as a learning medium to improve students' digital literacy. This study used a quasi-experimental design with purposive sampling, involving 67 students divided into experimental and control groups. The experimental group used Powtoon, while the control group used PowerPoint. Digital literacy was assessed through pre- and post-tests across five indicators: information, communication, content creation, security, and problem-solving. A t-test analysis showed significant differences across all indicators, with the experimental group showing a higher N-gain. The most significant improvement occurred in communication and security, highlighting Powtoon's role in fostering an interactive and engaging learning experience. These findings suggest that Powtoon is an innovative medium that enhances students' digital literacy while improving subject understanding. This study underscores the potential of integrating Powtoon into education to create a more dynamic and effective learning environment. This research suggests that using Powtoon as an innovative medium in physics learning can improve students' digital literacy and strengthen conceptual understanding through engaging and interactive visualizations. This demonstrates the importance of integrating creative technology into learning to support 21st-century skills.